PELATIHAN MANAJEMEN DIRI DAN LITERASI KEUANGAN PADA ANGGOTA CREDIT UNION - Widawati Hapsari; Kristiana Haryanti; Maria Braman Widyantari (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
COVID-19 pandemic affects every aspect of human life, including economic aspect. The government urged the implementation of social restriction policy, and as consequences, public activities are limited. According to Credit Union’s board members, there is an increase of loans rate since the social restriction begin. It is inevitable since essential needs are increasing and at the same time the financial conditions are unstable. All of the members in Credit Union Pangudi Luhur Kasih Semarang need to manage their financial issues properly regardless of their age especially in this pandemic time. Thus, this community service program aims to give better understandings to the members about the importance of self-management and financial literation by webinar.  Webinar was divided into three sections according to the audiences characteristics, members who had already married (n=100), close to pension age (n=334), and young member or singles (n=169). Based on the analyses, there is significant differences between pre-test and post-test score after conducting the webinar.